The Role of Auditors in the Banking Sector - Krishnan, Loganathan (Journal of Malaysian and Comparative Law, 2009)
The term ‘auditor’ originates from the expression ‘auditor’, which in Latin means ‘to listen’. Nevertheless when one scrutinises the duties of auditors, he will realise that auditors do not merely listen. They examine companies’ accounts and submit reports. These duties have augmented over recent years due to changing corporate atmosphere enveloping the business world including the banking sector. Thus this study reassesses auditors’ duties as there are specific laws governing auditors in the banking sector. The study examines whether the laws are adequate in ensuring that auditors are effective watchdogs. A comparative study is also carried out to investigate auditors’ duties in the non-banking sector. Essentially corporate law must ensure the interests of all stakeholders are well balanced with the challenging role of auditors.